2014
DOI: 10.1021/co400119c
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Anagrelide Sulfonyl Analogues

Abstract: Simple solid-phase synthesis of 3,10-dihydro-2H-benzo[e]imidazo[1,2-b][1,2,4]thiadiazin-2-one 5,5-dioxides is described, with Fmoc-α-amino acids and 2-nitrobenzenesulfonyl chlorides (2-NosCls) being the key building blocks. Fmoc-α-amino acids were immobilized on Wang resin and transformed to the corresponding 2-nitrobenzenesulfonamides in two steps. After reduction of the nitro group, Fmoc-thioureas were synthesized followed by cyclization of the 1,2,4-benzothiadiazine-1,1-dioxide scaffold with diisopropylcarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
(19 reference statements)
0
24
1
Order By: Relevance
“…Ion pairing between N + (C 4 H 9 ) 4 and S 2 O 4 2− makes the reducing agent soluble in organic media allowing it to diffuse to the nitro compounds. While it has been successfully used for solid-phase synthetic protocols [170,171], our tests reveal that this PTC approach does not produce 15 from 14 in acceptable yields.…”
Section: Selective Reduction Of Nitro Groups In Aa Conjugatesmentioning
confidence: 87%
“…Ion pairing between N + (C 4 H 9 ) 4 and S 2 O 4 2− makes the reducing agent soluble in organic media allowing it to diffuse to the nitro compounds. While it has been successfully used for solid-phase synthetic protocols [170,171], our tests reveal that this PTC approach does not produce 15 from 14 in acceptable yields.…”
Section: Selective Reduction Of Nitro Groups In Aa Conjugatesmentioning
confidence: 87%
“…A solid-phase synthesis of analogous BGs 187, based on the 3,10-dihydro-2H-benzo[e]imidazo [1,2-b] [1,2,4]thiazin-2one 5,5-dioxide scaffold, was described in 2014. [97] The target 6+5 compounds were synthesised from Fmoc-α-amino acids and 2-nitrobenzenesulfonyl chlorides. The synthesis was performed on Wang resin.…”
Section: Synthesis Of Bgs On a Polystyrene Supportmentioning
confidence: 99%
“…In our recent work, it was demonstrated that either full 19 or partial 20 racemization of the α-amino acid stereocenter can occur, even under mild reaction conditions. To evaluate the stereochemical outcome of this synthetic method, compound 7 DL (1,3,1,1) was prepared as the racemic standard.…”
Section: ■ Introductionmentioning
confidence: 99%